P wave dispersion in obsessive-compulsive disorder - Yavuzkir, Mustafa F.; Atmaca, Murad; Gurok, M. Gurkan; Adiyaman, Sahin (Medknow Publications & Media Pvt Ltd, 2015)
Background: P wave dispersion (Pd) is defined as the difference between the maximum and the minimum P wave duration. It has recently been associated with increased anxiety levels, thereby predisposing affected individuals to fatal heart disease. Despite of evidence of this autonomous nervous system (ANS) relationship, there are no electrocardiography (ECG) studies in the patients with obsessive-compulsive disorder (OCD). Thus, in this study, we aimed to evaluate the Pd in OCD patients. Materials and Methods: The study consisted of a total of 25 patients with OCD and same number of physically and mentally healthy age- and gender-matched controls. For psychological testing, Yale-Brown Obsession and Compulsion (Y-BOCS) was administered. Results: Pmax was found to be significantly higher in the patients compared to controls. Pmin did not differ between groups. Left atrium sizes were not different between groups. As for the main parameter investigated in the present study, it was found that Pd was significantly increased in the OCD patients than the controls. Y-BOCS scores for the patient group was positively correlated with Pd (r = 0.73, P < 0.01). Conclusions: In conclusion, our results suggest that Pd may be associated with OCD though our sample is too small to allow us to obtain a clear conclusion. Future studies with larger sample evaluating the effects of treatment are required.
Keywords: Autonomous nervous system; obsessive-compulsive disorder; P wave dispersion